2018
DOI: 10.3892/mmr.2018.9110
|View full text |Cite
|
Sign up to set email alerts
|

miR‑339‑5p negatively regulates loureirin A‑induced hair follicle stem cell differentiation by targeting DLX5

Abstract: Our previous study indicated that loureirin A induces hair follicle stem cell (HFSC) differentiation through Wnt/β-catenin signaling pathway activation. However, if and how microRNAs (miRNAs/miRs) modulate loureirin A-induced differentiation remains to be elucidated. In the present study, HFSCs were separated from the vibrissae of rats and identified by CD34 and keratin, type 1 cytoskeletal (K)15 expression. Microarray-based miRNA profiling analysis revealed that miR-339-5p was downregulated in loureirin A-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…MicroRNAs (miRs) are a family of short non-coding RNAs with the length of 21-24 nucleotides, which exert crucial roles in multiple cellular processes such as cell progression, proliferation and differentiation [10]. In particular, miR-214 and miR-125b have been found to operate as key mediators of HF maintenance in the telogen stage through their suppressive roles in HFSCs proliferation and differentiation [11]. Similarly, miR-19b-3p was confirmed to be associated with an enhanced proliferation of goat male germline stem cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRs) are a family of short non-coding RNAs with the length of 21-24 nucleotides, which exert crucial roles in multiple cellular processes such as cell progression, proliferation and differentiation [10]. In particular, miR-214 and miR-125b have been found to operate as key mediators of HF maintenance in the telogen stage through their suppressive roles in HFSCs proliferation and differentiation [11]. Similarly, miR-19b-3p was confirmed to be associated with an enhanced proliferation of goat male germline stem cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the quantity of HFSCs decreased in photoaging skin and increased after ADSCs transplantation. The transient quiescence of HFSCs after UVB irradiation may be a protective mechanism against photocarcinogenesis …”
Section: Discussionmentioning
confidence: 99%
“…The absence or malfunction of HFSCs is linked to a damaged initial healing response to full‐thickness injury of the skin in a mouse model . Evidence showed that adipose‐derived stem cells (ADSCs) enhance angiogenesis, re‐epithelialization, and extracellular matrix (ECM) deposition, which are essential to the restoration of skin protective screen function .…”
Section: Introductionmentioning
confidence: 99%
“…Instead of the association of these components with miRNAs as direct targets or regulators, the altered expression of filaggrin, involucrin, and loricrin is accompanied by changes in other differentiation markers and barrier proteins as described in keratinocyte differentiation associated with upregulation of miR-203 and miR-184 [20,23,32]. Downregulation of miR-339-5p increases levels of distal-less homeobox5 (DLX5), leading to involucrin upregulation via activation of the Wnt/β-catenin signaling pathway [91]. Dicer is involved in the regulation of skin barrier function [100].…”
Section: Filaggrin Involucrin Loricrin and Their Transcription Factorsmentioning
confidence: 99%